Alternative Approaches in Macroeconomics Essays in Honour of John McCombie (Springer International Publishing, 2018)
This book honours Professor John McCombie's retirement by exploring a variety of themes, theories and debates in non-orthodox macroeconomics. With contributions from leading scholars, the book covers diverse ground in economic thought, policy, empirical work and modelling. It demonstrates ongoing presumptions and asks probing questions of topical questions from the increase of income equality to the international variation of productivity investment. This collection will appeal to academics and students with an interest in the history of macroeconomic thinking.